BASELINE ASSESSMENT OF PROGRAMMING PERCEPTION AND READINESS AMONG SECONDARY SCHOOL STUDENTS IN EDO STATE - Osemwegie, Eric; Amadin, F. I.; Uduehi, O. M (FUDMA Journal of Sciences, 2025)
The study examined secondary school students’ readiness for programming in education in Edo State, Nigeria, with emphasis on curriculum gaps and students’ preparedness before full implementation of programming in the national curriculum. A descriptive survey design was adopted, and data were collected from 185 validly completed questionnaires distributed across public and private secondary schools. The instrument measured students’ perceptions, factors influencing readiness, and expectations toward programming education. Descriptive statistics (mean and standard deviation) and inferential tests (t-tests) were used for data analysis. Findings revealed that students’ perception of programming was neutral (Mean = 3.27), influenced by limited practical exposure and teacher engagement. Factors influencing readiness included personal confidence, teacher competence, and availability of ICT resources, with a moderate overall readiness level (Mean = 3.46). Students’ expectations were high (Mean = 3.71), showing enthusiasm toward learning programming and engaging in coding-related activities. Significant differences were found in perceptions across gender (p < 0.05), but not across school type. However, expectations differed significantly between public and private school students (p < 0.05). The study concluded that Edo State students demonstrated readiness for programming education but require improved teacher capacity, gender inclusion, and infrastructure to support effective curriculum delivery. Recommendations include enhanced teacher training, provision of ICT resources, and establishment of coding clubs to foster engagement and digital competence.